2008
DOI: 10.3171/jns/2008/108/2/0287
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery patients' feelings about the role of residents in their care: a qualitative case study

Abstract: Patients appear to be unaware of the role of residents in their surgical care but do not seem anxious about it. Trust in the medical system helps patients proceed with risky operations. Surgeons could be more forthcoming with patients about the role of residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 20 publications
0
31
1
Order By: Relevance
“…In our study, these 2 common situations of minimal resident supervision were associated with the lowest consent rates, with only 25.6% and 18.2% of patients indicating a willingness to consent to these respective scenarios. Many previous studies 5,6,9,15,16 of this issue have concluded with arguments for routine and detailed disclosure of information regarding trainee participation during the informed consent process but they provide no data estimating the potential effect of such a policy on consent rates. Our results raise significant concerns regarding the effect of such a policy on resident education and, in particular, the effect on allowing increased levels of autonomy to trainees.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, these 2 common situations of minimal resident supervision were associated with the lowest consent rates, with only 25.6% and 18.2% of patients indicating a willingness to consent to these respective scenarios. Many previous studies 5,6,9,15,16 of this issue have concluded with arguments for routine and detailed disclosure of information regarding trainee participation during the informed consent process but they provide no data estimating the potential effect of such a policy on consent rates. Our results raise significant concerns regarding the effect of such a policy on resident education and, in particular, the effect on allowing increased levels of autonomy to trainees.…”
Section: Commentmentioning
confidence: 99%
“…Several recent studies [5][6][7] have pointed out the paucity of information typically provided to the patient regarding trainee participation; those studies call for this information to become a standard and universal component of informed consent. However, the specifics of such a policy and their potential effect on the patient and the trainee remain unknown.…”
mentioning
confidence: 99%
“…The importance of trust has not surprisingly been reported to be very important for patients participating in many other qualitative studies [3, 11]. Because this surgery would be a second or third surgery, presumably the patient would have earned trust in his/her surgeon, since they got the patient through it the first time.…”
Section: Discussionmentioning
confidence: 99%
“…reduces the anxiety of patients 8,9 , improves decision making [10][11][12] , and increases adherence to the oncologist's recommendations [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%